Web Archiving: Issues and Problems in Collection Building and Access - Jacobsen, Grethe (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Denmark began web archiving in 2005 and the experiences are presented with a specific focus on collection-building and issues concerning access. In creating principles for what internet materials to collect for a national collection, one can in many ways build on existing practice and guidelines. The actual collection requires strategies for harvesting relevant segments of the internet in order to assure as complete a coverage as possible. Rethinking is also necessary when it comes to the issue of description, but cataloguing expertise can be utilised to find new ways for users to retrieve information. Technical problems in harvesting and archiving are identifiable and can be solved through international cooperation. Access to the archived materials, on the other hand, has become the major challenge to national libraries. Legal obstacles prevent national libraries from offering generel access to their archived internet materials. In Europe the principal obstacles are the EU Directive on Data Protection (Directive 95/46/EC) and local data protection legislation based on this directive. LIBER is urged to take political action on this issue in order that the general public may have the same access to the collection of internet materials as it has to other national collections.